A retro‐prospective effectiveness study on 3448 implant operations at one referral clinic: A multifactorial analysis. Part I: Clinical factors associated to early implant failures. (8th September 2017) - Jemt, Torsten
Abstract: Background: Limited numbers of large effectiveness studies on routine dental implant treatment are available in the literature. Purpose: To report retro‐prospective data on prevalence of early implant failures in a large number of routine patients/operations at 1 referral clinic. Materials and methods: A total of 2848 patients were consecutively provided with 9582 implants with an anodized surface (Nobel Biocare AB) during 3448 implant operations between 2003 and 2011. All patients were invited to a follow‐up program and early implant failures up to first annual examination were consecutively identified. A logistic multivariate data analysis was performed to identify possible factors with an association to early implant failures. Results: A total of 43, 73, and 81 implant operations were denoted as early failures depending on when cut‐off time was defined, using: abutment connection, prosthesis placement, or at first year of follow‐up, respectively. Five factors showed significant association to "early implant failures, " where the highest risk for a failure was associated to "surgeon" (hazard ratio [HR] 5.13), followed by "not prosthetic treatment at the referral clinic" (HR 2.71). When all 5 significant factors were present, the risk for an early failure after an operation was 7.0%, and the risk decreased to 0.1% when none/lowest risk factors were present. Conclusions: The role of the surgeons/dentists involved in the rehabilitation of the implant patients and numbers of placed implants (degree of tooth loss) showed the strongest associations to early implant failures in the present clinic. Also increased bone resorption was associated to increased risk for implant failure.